The ∞-fučík spectrum - Rossi, Julio Daniel (2018)
In this article we study the behavior as p % +∞ of the Fučik spectrum for pLaplace operator with zero Dirichlet boundary conditions in a bounded domain Ω ⊂ Rn. We characterize the limit equation, and we provide a description of the limit spectrum. Furthermore, we show some explicit computations of the spectrum for certain configurations of the domain